Novel USP18 mutations lead to severe interferonopathy responsive to JAK inhibitor - Sun, Xiangwei; Li, Ming; Dou, Yiying; Wang, Qintao; Lai, Jianming; Zhu, Jia; Zhou, Qing; Yu, Xiaomin (Frontiers in Immunology, 2025)
IntroductionUbiquitin-specific peptidase 18 (USP18) is a key negative regulator of type I interferon (IFN) signaling. USP18 deficiency resulted in embryonic or neonatal lethality with severe systemic inflammation and neurological anomalies due to excessive IFN signatures. Importantly, additional disease-causing USP18 mutations remain to be identified and functionally characterized.MethodsWhole-exome sequencing was performed to identify pathogenic variants in two affected individuals. Extensive immunologic and functional assay were used to characterize inflammatory signatures and evaluate the impact of the variants on type I IFN signaling. Therapeutic intervention with the JAK inhibitor was administered and clinical response was monitored.ResultsWe identified novel USP18 biallelic mutations (p.C230X and p.G317S) in siblings with severe early-onset systemic inflammation. Patient PBMCs exhibited hypersensitivity to IFNα, leading to aberrant and prolonged activation of type I IFN signaling. Mechanistic studies revealed that the p.G317S variant disrupted the interaction between USP18 and ISG15, thereby impairing its negative regulatory function. Treatment with JAK inhibitor ruxolitinib alleviated the inflammatory phenotypes, followed by a sustained recovery.ConclusionNovel biallelic mutations of USP18 lead to excessive type I IFN responses and severe interferonopathy. Our findings highlight a novel pathogenic mechanism in which impaired ISG15 binding compromises the regulatory function of USP18. The favorable clinical response to ruxolitinib suggests a promising therapeutic strategy.